2005
DOI: 10.1002/app.21999
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of sodium ion implanted poly(vinyl alcohol) films

Abstract: Poly(vinyl alcohol) (PVA) films were implanted with sodium ions at various energies and total doses. Modified films were characterized by Fourier transform IR (FTIR), UV-visible (UV-vis), X-ray diffraction (XRD), and scanning electron microscopy (SEM). From FTIR studies, it was evident that scission of the main chain occurred together with removal of hydrogen and hydroxyl groups. Sodium ions formed weak bonds with oxygen from the neighboring chains. UV-vis studies of implanted PVA showed increases in the absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…3(a)) with some particles at random on the surface with varying sizes. Such a structure is characteristic of PVA surface and agrees well with our earlier studies [12]. Fig.…”
Section: Morphological Studies Using Semsupporting
confidence: 89%
See 1 more Smart Citation
“…3(a)) with some particles at random on the surface with varying sizes. Such a structure is characteristic of PVA surface and agrees well with our earlier studies [12]. Fig.…”
Section: Morphological Studies Using Semsupporting
confidence: 89%
“…However, this band in the spectra of implanted PVA samples, which were normalized and smoothened, showed good resolution of bands. Such splitting of bands was also observed in our earlier work for irradiated PVA using sodium ions [12]. It was found that the area under the curve for the -OH band decreased to some extent after the irradiation.…”
Section: Ftir Analysissupporting
confidence: 60%
“…1 and 2 show the SEM images of control, annealed and plasma treated PVA films at 500× and 3000× magnifications. It could be seen that the morphology of the control was very smooth only with some dust particles as reported in previous studies [30,31]. Some salt grains were observed on the annealed film surface, which was still smooth.…”
Section: Sem Analysissupporting
confidence: 59%
“…According to the energy potentials, the wavenumber (or frequency) at which broad O−H stretching vibration occurs increases as the O−H bond strength increases. , From this viewpoint, the O−H bond in PVOH becomes stronger as IL is added. The change in O−H bond strength of PVOH in the presence of IL suggests that IL interacts with the hydroxyl group of PVOH, forming IL−PVOH complex . The resulting IL−PVOH complex is likely to exist as aggregates with low degree of order, considering the asymmetric, bulky structure of the IL.…”
Section: Resultsmentioning
confidence: 99%